Regulation of specific surface area of 3D flower-like WO3 hierarchical structures for gas sensing application. Issue 8 (1st June 2020) - Xu, Wei; Qiu, Changjun; Zhou, Juan; Chen, Yong
Abstract: The 3D flower-like WO3 nanoparticles with hierarchical structures were synthesized via a hydrothermal synthesis technique by using NaHSO4 as a capping agent. It demonstrates that surface area of the synthesized WO3 products can be manipulated via adjusting concentration of the capping agent NaHSO4 alone. The contribution of alcohol is to construct hierarchical structures with large specific surface areas, while the effect of SO4 2− is to inhibit the growth rate in the thickness direction of nanosheets which are self-assembled as well to form hierarchical structures. In addition, the gas-sensing property of sensors fabricated by 3D flower-like hierarchical structured WO3 nanoparticles were carried out by detecting different volatile gases with a lower concentration. All the samples are sensitive to ethanol gas and the WO3 3D flowers synthesized by 12 g NaHSO4 exhibit the excellent gas-sensitive property due to the highest surface area, the sensitivity as high as 96 under the concentration of 35 ppm at the optimal temperature of 350 °C, which implies that this 3D hierarchical structured WO3 nanoparticles could be used as a high-efficiency sensor candidate materials for selective detection of ethanol.